Scope of İnnovative and Smart Tourism in Kullu and Kinnaur Districts of Himachal Pradesh - Prince Robin Krishna Murti (International Journal of Advanced Science and Technology, 2020)
The purpose of this paper is to present the findings of a research study conducted to know the perception of tourists who visit Himachal Pradesh and nearby region about adoption of using innovative and smart tourism in the region of kullu and kinnaur district. Its benefits, triggers & barriers with respect to sustainability and help in upliftment of local residents’ lives in long term. It presents how with the amalgamation of smart equipment with the community organized cultural and food festivals the current footfall could be re-wired. In this research we will know why the Perspective of Indian government about promoting tourism in less popular areas by concentrating on the Value for money, comfort and accessibility, entertainment/nightlife, sustainability and political history of any place need a refined touch of technology and innovation. There is a need to conduct further research since today the passengers want to witness unique experiences and beyond the service that one can provide. This includes in the offer interactive or immersive experiences that can later have a replication in real life and in an unforgettable moment transform the traveling experience. New technologies make these unique experiences easier for consumers to enjoy, which is important in a sector such as tourism. There, emotions and feelings are part of the overall experience and will help to determine the satisfaction level.